Soft Robotics: A Magnetically Coupled Dielectric Elastomer Pump for Soft Robotics (Adv. Mater. Technol. 8/2019). Issue 8 (8th August 2019) - Cao, Chongjing; Gao, Xing; Conn, Andrew T.
Abstract : A pneumatic diaphragm pump driven by a magnetically‐coupled dielectric elastomer actuator is proposed by Chongjing Cao, Xing Gao and Andrew Conn in article number1900128 . It exploits a compliant coupling between membranes to resonate at high power and efficiency. The flexible pump is demonstrated driving soft robotic prototypes including a soft gripper, ballooning chamber, and suction cup.